UTILIZATION OF SOCIAL MEDIA FOR MARKETING AND PROMOTION USING FACEBOOK IN THE COMMUNITY PARUNG SERAB CILEDUG - Emi Sita Eriana; Imam Hidayat; Reza Rizki Romadhon; Fazar Azmal; Vibra Ikhwan Ramadhan; Wawan Ivpani (Yayasan Education and Social Center, 2021)
The development of Social Media is now very rapid where initially social media is only used as a means of communicating and pulikasi; now it becomes a media that has a broader benefit that makes social media as a means of marketing and promotion, along with the increasing internet users in the world, especially in Indonesia, currently the population of Indonesia becomes the 3rd largest Facebook user worldwide. Therefore Facebook social media becomes one of the marketing and promotional facilities that have excellent prospects today. By utilizing one of the marketplace features that exist on social media, Facebook parung Serab community can do business with minimal capital, unlimited time and reachability that not only reaches the local scale but also reaches the global scale, So this is what concerns us the implementing team to motivate the people of Parung Serab to use Social Media Facebook as a marketing and promotional media, namely by teaching the practical use of social media Facebook, marketing strategies on social media Facebook to how to apply